Jack Surgery: Reconstructing Collapsed Femoral Head in Association Research Circulation Osseous Stage III Osteonecrosis: A Series of 13 Cases - Ying Zhong; Yichen Gong; Shuaijie Lv; Wenxi Du; Xun Liu; Jianhua Zhang; Peijian Tong (Orthopaedic Surgery)
ABSTRACT Objective According to Association Research Circulation Osseous (ARCO) staging, patients with ARCO III osteonecrosis of femoral head (ONFH) have joint pain and dysfunction due to the collapse of femoral head. Current hip preservation surgeries are not satisfying in the treatment of ARCO III ONFH according to the long‐term follow‐up. In our practice, we focused on reconstructing femoral head by restoring the round shape of femoral head and subsequently preventing the development of hip arthritis. To lift the collapsed femoral head and postpone the potential total hip arthroplasty, we practiced Jack surgery, combining surgical hip dislocation, removal of necrotic bone, impaction bone grafting, and lifting the cartilage of femoral head. Methods From February 2019 to July 2022, 13 patients (15 hips) who received Jack surgery in the research center were included in this retrospective study. Follow‐up was conducted every 3 months after surgery for imaging and clinical evaluation. The differences between visual analogue scale (VAS) and Harris hip score (HSS) before and after surgery were compared to observe whether the femoral head collapsed and whether osteotomy healed after surgery. Severe collapse of the femoral head ( > 2 mm) or receiving total hip arthroplasty (THA) was defined as failure of hip preservation therapy. An Independent sample t‐test was used to compare the data, and the chi‐square test was used for categorical data. Results All the 13 patients successfully completed the surgery and were followed up. The average time of follow‐up was 36.46 ± 16.87 months (ranging from 14 to 66 months). HSS was assessed 12 months after surgery: excellent in 1 patient with 1 hip; good in 9 patients with 11 hips; modest in 3 patients with 3 hips. To the last follow‐up, the VAS scores decreased from 6.17 ± 1.02 to 2.08 ± 0.90 (p < 0.001), HSS increased from 46.69 ± 4.15 to 89.77 ± 2.86 (p < 0.001). No deep infection, fracture, osteotomy nonunion, nerve injury, deep vein thrombosis, pulmonary embolism, or other complications occurred. Conclusion For young patients with ONFH of ACRO III, this surgical technique can effectively restore the original shape of the femoral head and achieve satisfactory hip function in the short term. The mechanism is similar to jacking the roof of a house; thus, we named it “Jack surgery”.